Imaging opioid analgesia in the human brain and its potential relevance for understanding opioid use in chronic pain. - Lee, M; Wanigasekera, V; Tracey, I (2014)
Opioids play an important role for the management of acute pain and in palliative care. The role of long-term opioid therapy in chronic non-malignant pain remains unclear and is the focus of much clinical research. There are concerns regarding analgesic tolerance, paradoxical pain and issues with dependence that can occur with chronic opioid use in the susceptible patient. In this review, we discuss how far human neuroimaging research has come in providing a mechanistic understanding of pain relief provided by opioids, and suggest avenues for further studies that are relevant to the management of chronic pain with opioids. This article is part of the Special Issue Section entitled 'Neuroimaging in Neuropharmacology'.